Glycoprotein P pharmacogenetic assessment role in digoxin pharmacotherapy individualization: a new approach for an old problem - D. A. Sychev; I. V. Ignatiev; D. A. Andreev; L. G. Poshukaeva; P. V. Kolkhir; E. E. Zhukova; V. G. Kukes (Российский кардиологический журнал, 2006)
The aim of the study was to investigate effects of glycoprotein P-coding gene MDR1 polymorphic marker C3435T on digitalis intoxication symptoms and plasma digoxin concentration increase in patient with persistent atrial fibrillation (AF). In 103 AF patients, genotyping by gene MDR1 polymorphic marker С3435T was performed in polymerase chain reaction (PCR). Balance plasma digoxin concentration was measured by polarizing fluoro-immune assay in 29 participants. Results: Plasma digoxin concentration was higher in TTgenotype patients, comparing to CC and CT genotype individuals (l,77 ± 0,17vs 1,17 ± 0,21, p = 0,02; 1,77 ± 0,17 vs 1,37 ± 0,30, p = 0,037, respectively). Glycoside intoxication syndromes were more prevalent in TTgenotype than in CC and CT genotypes (57 % vs 13 %, p = 0,0001, OR = 6,4, CI 1, 9-21,9). Therefore, TT genotype of glycoprotein P-coding gene MDR1 polymorphic marker C3435T, was associated more frequent symptoms of glycoside intoxication and higher plasma digoxin levels.